(untitled) (Jurnal Bina Praja, 2022)
The relationship between the environment and economy and people’s consumption is still contradictory in efforts to save the environment. Excessive consumption and production patterns lead to polluted rivers. This qualitative research aims to describe the management of the Batang Arau watershed from a GEG perspective. Primary data was collected with in-depth interviews regarding the condition. Secondary data was obtained study of documentation related to laws and regulations. Informants are determined by the purposive sampling method (Sugiyono, 2017). Informants are parties related to the watershed. Data obtained were analyzed with Manual Data Analysis Procedure (MDAP) technique 1. Results showed the management of the Batang Arau watershed had not been implemented following principles of Good Environmental Governance; findings in the field found that; Public awareness is low, the law of environmental protection has not been optimal, and access to industrial waste information has not been opened, the government response is quite good, and environmental consensus has not been reached, there is a sectoral ego, a long bureaucratic path, environmental responsibility is lacking. Constraints, unified management vision among stakeholders, insufficient budget and fleet, low supervision, IPAL facilities have not integrated, Illegal logging, and inter-sectoral coordination are still problematic. Efforts made by the government: Conducting socialization to the community, cleaning and dredging watershed, and normalizing and rehabilitating critical land. Management must be carried out thoroughly, so there is no gap between upstream and downstream. We argue to create a balanced ecosystem. The government needs to improve management as a whole with a Good Environmental Governance approach in every management action to create sustainable management.